Intelligent remote/trigger : a photographer's buddy (Arduino based) - Leong, Jian Hao (2019)
High speed photography is an activity that is enjoyed by many photographers. The amount of time and effort spent on getting the perfect shot is incredible, where they might have to try hundreds or even thousands of attempts. While there are many commercial equipment and devices available in the market to aid them, many of which are either lacking in functionality or just have portability issues. The project aims to extend the functionality that was previously developed by past FYP students and to produce a system that’s not only capable of setting up high speed scenarios and is portable enough to be easily carried around during a shoot.